Decision Making and Implementation of the First Public Sector Introduction of Typhoid Conjugate Vaccine—Navi Mumbai, India, 2018. (29th July 2020) - Date, Kashmira; Shimpi, Rahul; Luby, Stephen; N, Ramaswami; Haldar, Pradeep; Katkar, Arun; Wannemuehler, Kathleen; Mogasale, Vittal; Pallas, Sarah; Song, Dayoung; Kunwar, Abhishek; Loharikar, Anagha; et al.
Abstract: Background: Typhoid fever prevention and control efforts are critical in an era of rising antimicrobial resistance among typhoid pathogens. India remains one of the highest typhoid disease burden countries, although a highly efficacious typhoid conjugate vaccine (TCV), prequalified by the World Health Organization in 2017, has been available since 2013. In 2018, the Navi Mumbai Municipal Corporation (NMMC) introduced TCV into its immunization program, targeting children aged 9 months to 14 years in 11 of 22 areas (Phase 1 campaign). We describe the decision making, implementation, and delivery costing to inform TCV use in other settings. Methods: We collected information on the decision making and campaign implementation in addition to administrative coverage from NMMC and partners. We then used a microcosting approach from the local government (NMMC) perspective, using a new Microsoft Excel–based tool to estimate the financial and economic vaccination campaign costs. Results: The planning and implementation of the campaign were led by NMMC with support from multiple partners. A fixed-post campaign was conducted during weekends and public holidays in July–August 2018 which achieved an administrative vaccination coverage of 71% (ranging from 46% in high-income to 92% in low-income areas). Not including vaccine and vaccination supplies, the average financial cost and economic cost per dose of TCV delivery were 0.45 and 1.42, respectively. Conclusion: The first public sector TCV campaign was successfully implemented by NMMC, with high administrative coverage in slums and low-income areas. Delivery cost estimates provide important inputs to evaluate the cost-effectiveness and affordability of TCV vaccination through public sector preventive campaigns.